Mysterious murder in musical Macbeth - Jamae, Albert (Kilkenny, SA : Moore Books SA, 2014)
With quirky chorus members, a bitter has-been-thespian janitor, and the henchman's stage debut, the rollercoaster of the evening's events prove at least one thing... you really shouldn't name that Scottish play!
Keywords: Australian drama -- South Australia -- 21st century; Australian